The Role Of Posyandu Cadres In Empowering Communities With Infectious Diseases In Petir District - Nazareni, Rindu Putri; Wahyunengsih, Wahyunengsih (Institut Agama Islam Negeri (IAIN) Kudus, 2024)
Indonesia ranks third out of eight countries contributing 2/3 of TB (tuberculosis) cases in the world. DHF is a disease that spreads not from one human to another, but from the Aedes Aegypti mosquito. The role of cadres in empowering the infectious disease community is urgently needed as an intermediary for sources of information from medical personnel. Cadres are not only as Posyandu or Posbindu services but cadres can also help medical personnel to turn residents into healthy communities. The purpose of this study was to find out whether Posyandu Cadres and health workers in had carried out their duties to make the community a healthy society or not, and whether they had been optimal in dealing with infectious diseases and also how the cadres worked in handling infectious diseases. The method used in this study is a qualitative method, namely by interviewing one of the cadres in the village of Rt.06 Petir and also the second method, namely by observation. The cadres have worked according to their capacity and have done well, and maybe in the future it will be even better. The results of this research have implications for policy development and implementation of dengue fever eradication programs. Apart from that, finding cadres who have carried out their duties in accordance with their capacity and standard procedures can improve cooperative relations with other related cadres and institutions.